Cognitive Film Theory : An Insider’s Appraisal - Plantinga, Carl (Cinémas, 2002)
ABSTRACTThis article appraises the contributions of what has been called cognitivism or the cognitive approach to film studies, and suggests the means by which the cognitive approach can become more central to film studies than it has been so far. The author first shows that much of what has been called "cognitivist" film studies is only cognitivist in a broad sense, and could just as well be called "analytic." He then argues that the cognitive approach would be most useful when it is thus broadly applied, becoming then more a commitment to the rationality of discourse and human thought than a narrow project within psychology. The article then goes on to appraise the utility of the cognitive approach in our understanding of the psychological power of film and film aesthetics.